Breastfeeding practices and its determinants: a descriptive cross sectional study in Aligarh - Chauhan, Ambren; Shah, M. Salman; Khalique, Najam; Eram, Uzma; Nagesh, Seetha Ramiah (International Journal Of Community Medicine And Public Health, 2020)
Background: The study was aimed to study the practices related to breastfeeding among newborns in Aligarh and to assess the determinants of breastfeeding practices. Methods: A cross sectional study was carried out in the field practice areas of Department of Community medicine, AMU, Aligarh. All the live births in one-year study duration were included in the study. Verbal consent was obtained prior to the interview. Data was collected by interview technique using semi structured questionnaire and analysed in SPSS 20. Results: A total of 705 newborns were enrolled in the study. 5.3% of the mothers in our study didn’t breastfeed their newborns even after 24 hours after the delivery. 6% of the mothers discarded their colostrum and 36.9% of mothers gave prelacteals to their newborns. Almost half of the newborns were exclusively breastfed. There is a significant association between being primiparous and not practicing exclusive breastfeeding (p=0.003). However, no significant association was found between breastfeeding practices and gender, birth order of newborn, age and education of mother. Conclusions: Present study shows that 64.2% of newborns received the right breastfeeding practices which is quite good as per the national average. This study emphasizes the need to address the practices like discarding the colostrum and use of prelacteal feed which are still widely prevalent.